DISTINCTIVE FEATURES OF EMOTIONAL INTELLIGENCE IN THE PROFESSIONAL ACTIVITIES OF FUTURE TEACHERS - Xo’jamova Shoxida Alpomish qizi (European Journal of Humanities and Educational Advancements, 2023)
This article cites the specifics of emotional intelect development during the professional activities of future teachers and their successful activity in interpersonal relationships, and the views of some researchers in this regard.